Effects of remote patient management on self-care behaviour in heart failure patients: results from the TIM-HF2 trial. (2nd July 2022) - Deckwart, O; Koehler, K; Lezius, S; Prescher, S; Koehler, F; Winkler, S
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German Federal Ministry of Education and Research Background: Remote patient management (RPM) in heart failure (HF) patients is a rapidly developing field of digital cardiology with beneficial clinical effects. RPM might affect HF specific self-care behaviour, which represents an important patient-reported outcome. Purpose: To investigate the effects of RPM used in the Telemedical Interventional Management in Heart Failure II (TIM-HF2) trial on HF-specific self-care as a prespecified secondary endpoint analysis. Methods and Results: HF patients who were recently hospitalized and do not suffer from major depression were randomized to either RPM plus Usual Care (UC) or UC only, with a 12-month follow-up. Self-reported self-care behaviour at baseline and study-end were assessed by mean differences of the 9-item European Heart Failure Self-care Behaviour Scale (EHFScBS-9). 1, 538 HF patients (mean age 70.3±10.5 years, 70% men, 52% NYHA class II and 47% NYHA class III, 65% LVEF ≤45%) were included, obtaining 1, 321 patients with valid baseline and follow-up questionnaires. Self-care behaviour sum scores increased in the RPM group (n=667) from 78.7±17 to 84.5±14 and in the UC group (n=654) from 79.0±17 to 80.0±16 from baseline to 12 months (mean difference 4.58 95% CI 3.02, 6.14; p<0.001). The subgroup of patients living alone and having an inadequate (<70) baseline self-care behaviour score showed the highest improvement (8.66[3.52; 13.81]). There were significant changes between both groups in item "I weight myself every day" (MD -1.13; 95% CI -1.24, -1.02; p<0.001), and item "I take my medication as prescribed" (MD -0.06; 95% CI -0.10, -0.01; p=0.014). No relation was found between the self-care behaviour score and the efficacy of RPM on the primary and main secondary endpoints of the TIM-HF2 study. Conclusions: RPM improves HF-specific self-care behaviour by achieving a better adherence to recommended HF regimen. Clinical endpoints were not affected by the level of self-care behaviour.